FEATURES OF THE NERVOUS SYSTEM AND MANIFESTATIONS OF ENURESIS IN CHILDREN (Herald of the National Children's Medical Center, 2022)
Enuresis is a very common problem in children, accompanied by impaired social adaptation, thereby reducing thequality of life and self-con=dence of children with this pathology. Treatment of bedwetting is a rather complicated problemthat requires correct diagnosis. This article studied the causes of enuresis and the use of a complex of drug and non-drugtreatment with elements of acupuncture, herbal medicine and their results.
Keywords: Enuresis; children; morbidity; treatment; neurosis; acupuncture; herbal medicine